Peningkatan Keterampilan Berpikir Kritis dan Hasil Belajar Siswa SD dengan Menerapkan Strategi Everyone Is A Teacher Here pada Model Pembelajaran Kooperatif - Yusuf, Mochamad (Jurnal Ilmiah Sekolah Dasar, 2018)
The purpose of this research was assess the activity of teachers, students, enhancement of critical thinking skils student,  results cognitive study, and to know student respon for learning that applied “Everyone  is a Teacher Here”strategy for cooperative models. Research used Classroom Action Research (CAR)methods. The subjects and the location of research was fourth grade students of  Hidayatul Mubtadiin Primary School, amounting to 26 students.The instrument used in this research consisted of sheet of observation teachers activities, sheets of observation of students avtivities, critical thinking skills test, cognitive results studies test, sheets of observation of afective results studies test, sheets of observation of psicomotoric results studies test, and sheets of respons students. The result showed that the activity of teacher, students, critical thinking skills, and the student’s results  study was increase significantly during two cycles with their respective percentage of completeness. Learning of applying “Everyone  is a Teacher Here” strategy for Cooperative models got positive respons from students so worthy to be applied by the teacher.